Artificial Intelligence (AI) as A Virtual Laboratory Assistant in Science Learning: A Literature Review - Said Wahyudi; M. Salsabillah Hidayah; M. Gita Ahzami (Indonesian, 2026)
This study aims to examine the role of Artificial Intelligence (AI) as a virtual laboratory assistant in science learning through a literature review approach. The rapid development of digital technology has transformed science education, particularly in laboratory activities that traditionally rely on physical facilities. The method used in this study is a literature review by analyzing various scientific articles obtained from Google Scholar using keywords related to AI, virtual laboratories, and science learning. The results indicate that AI as a virtual laboratory assistant can provide experimental guidance, automatically analyze data, and deliver immediate feedback to students. Furthermore, the integration of AI in virtual laboratories and virtual reality enhances conceptual understanding, science process skills, and students' learning motivation. However, the implementation of this technology still faces challenges such as limited infrastructure, digital literacy, and teachers’ readiness. Therefore, further development and implementation of AI-based virtual laboratories are necessary to support more effective, interactive, and inclusive science learning.